2016
DOI: 10.1104/pp.16.00852
|View full text |Cite
|
Sign up to set email alerts
|

FUM2, a Cytosolic Fumarase, Is Essential for Acclimation to Low Temperature in Arabidopsis thaliana

Abstract: Although cold acclimation is a key process in plants from temperate climates, the mechanisms sensing low temperature remain obscure. Here, we show that the accumulation of the organic acid fumaric acid, mediated by the cytosolic fumarase FUM2, is essential for cold acclimation of metabolism in the cold-tolerant model species Arabidopsis (Arabidopsis thaliana). A nontargeted metabolomic approach, using gas chromatography-mass spectrometry, identifies fumarate as a key component of the cold response in this spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
92
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(100 citation statements)
references
References 37 publications
(54 reference statements)
6
92
1
1
Order By: Relevance
“…Because FUM2 is less highly induced by exogenous ABA in srk2d srk2e srk2i and areb than in wild type (Supplemental Figure 12), FUM2 expression in response to ABA might be regulated by the SnRK2-AREB/ABF signaling pathway. Intriguingly, FUM2 was recently shown to be essential for acclimation to low temperature, as the fum2 mutant is unable to modify its photosynthetic rate in response to the cold (Dyson et al, 2016). This is interesting in light of this study because of the similarities in the regulation of the responses to cold and osmotic stress and the finding that ABA is involved in both processes .…”
Section: Carbon Metabolism Is Regulated By the Snrk2 Kinasesmentioning
confidence: 85%
“…Because FUM2 is less highly induced by exogenous ABA in srk2d srk2e srk2i and areb than in wild type (Supplemental Figure 12), FUM2 expression in response to ABA might be regulated by the SnRK2-AREB/ABF signaling pathway. Intriguingly, FUM2 was recently shown to be essential for acclimation to low temperature, as the fum2 mutant is unable to modify its photosynthetic rate in response to the cold (Dyson et al, 2016). This is interesting in light of this study because of the similarities in the regulation of the responses to cold and osmotic stress and the finding that ABA is involved in both processes .…”
Section: Carbon Metabolism Is Regulated By the Snrk2 Kinasesmentioning
confidence: 85%
“…Recently, Dyson et al . have provided compelling evidence that AtFUM2 is essential for A. thaliana acclimation to low temperatures. Moreover, biomass production at low temperatures exhibits a surprisingly high positive correlation with AtFUM2 transcript and fumarate levels .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that gene duplication has constituted the raw material for the adaptive evolution of new species, the processes by which duplicated genes become fixed in the genome were based on their ability to acquire either subfunctionalization or neofunctionalization [46]. Recently, Dyson et al [47] have provided compelling evidence that AtFUM2 is essential for A. thaliana acclimation to low temperatures. Moreover, biomass production at low temperatures exhibits a surprisingly high positive correlation with AtFUM2 transcript and fumarate levels [48].…”
Section: Cytosolic Fum2 Could Be Present In Other Plant Species As a mentioning
confidence: 99%
“…An explanation for these differences might be the recently described and naturally occurring promotor polymorphism of the Arabidopsis FUM2 gene (Riewe et al, 2016). The cytosolic fumarase, FUM2, catalyses the cytosolic interconversion of malate to fumarate and was shown to be essential for cold acclimation in Arabidopsis (Dyson et al, 2016). Riewe and colleagues found that the insertion/deletion polymorphism was absent from the promotor region of Columbia-0 FUM2, yet present in the C24 promotor region.…”
Section: Discussionmentioning
confidence: 99%